Lesbian feminism: Essays opposing global heteropatriarchies - Banerjea, Niharika; Browne, Kath; Ferreira, Eduarda; Olasik, Marta; Podmore, Julie (Zed Books, 2019)
S'appuyant sur l'incroyable richesse de la diversité des langues, des cultures et des mouvements dans lesquels les féminismes lesbiens se sont articulés, ce livre confronte la dévalorisation historique de la politique lesbienne-féministe au sein du discours anglo-américain et déclenche une discussion transnationale et transgénérationnelle sur la pertinence des féminismes lesbiens. dans le monde d'aujourd'hui, une discussion qui remet en question la vision du féminisme lesbien comme statique et essentialiste. En examinant attentivement les débats contemporains, ces écrivai.n.es, théoricien.n.e.s, universitaires et militant.e.s examinent la place plus large des féminismes lesbiens au sein de la théorie queer, du féminisme postcolonial et du mouvement pour les droits LGBT. Il examine comment les féminismes lesbiens peuvent contribuer aux discussions sur l'intersectionnalité, s'engager dans l'activisme trans et le besoin de trans-inclusion, pour finalement montrer comment les féminismes lesbiens peuvent offrir une approche transformatrice des politiques sexuelles et de genre d'aujourd'hui.
Keywords: approches et analyses; discours dominant; histoire et politique; identités LGBTQIA2+; intersectionnalité; lesbianisme; outils; ouvrages de références; personnes trans*; systèmes d'oppressions; thématiques

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Protocole de recherche des Premières Nations au Québec et au Labrador - Basile, Suzy (Assemblée des Premières Nations du Québec et du Labrador, 2014)
« Ce protocole de recherche est en premier lieu un instrument collectif pour les chefs et les gestionnaires des communautés qui sont invités à participer à des projets de recherche ou à collaborer à ceux-ci. Cet instrument sert de guide aux Premières Nations, aux communautés et aux organisations régionales des Premières Nations, mais aussi indirectement à la communauté scientifique, afin de réglementer et encadrer les activités de recherche qui se déroulent sur le territoire des Premières Nations ou auprès de leur peuple respectif. […] [C]et instrument n’est pas un substitut aux outils, politiques ou guides existant au sein des Premières Nations, des communautés et des organisations des Premières Nations. Nous réitérons le fait que les Premières Nations doivent exercer leur gouvernance en matière de gestion de l’information et des connaissances collectives et qu’elles ont la responsabilité de protéger et de conserver leur patrimoine informationnel. Cet instrument est donc un outil supplémentaire pour poursuivre les actions entreprises dans ce secteur ». [Résumé original]
Keywords: amériques; approches et analyses; autochtones; canada; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; recherche collaborative; recherche en milieux de pratique; recherche partenariale; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Sovereign erotics: A collection of Two-Spirit literature - Driskill, Qwo-Li; Justice, Daniel Heath; Miranda, Deborah; Tatonetti, Lisa (The University of Arizona Press, 2011)
Les personnes bispirituelles, identifiées par de nombreux noms et positions tribales spécifiques au sein de leurs communautés, vivent, aiment et créent de l'art depuis des temps immémoriaux. Ce n’est cependant que dans les années 1970 que la littérature autochtone queer contemporaine a attiré l’attention du public. Même aujourd’hui, seule une poignée de livres en parlent spécifiquement, notamment la collection de 1988 Living the Spirit: A Gay American Indian Anthology. Depuis la publication de ce livre il y a vingt-trois ans, aucune autre collection n'a été publiée se concentrant explicitement sur l'écriture et l'art des peuples autochtones bispirituels et queer. Cette collection historique s'efforce de refléter la complexité des identités au sein des communautés autochtones gaies, lesbiennes, bisexuelles, transgenres, queer et bispirituelles (GLBTQ2). Rassemblant le travail d'écrivains confirmés et de nouvelles voix talentueuses, cette anthologie couvre les genres (fiction, non-fiction, poésie et essai) et les thèmes (mémoire, histoire, sexualité, indigénéité, amitié, famille, amour et perte) et représente un tournant décisif. moment dans les littératures amérindiennes et autochtones, les études queer et les intersections entre les deux. En collaboration, les pièces de Sovereign Erotics démontrent non seulement la diversité radicale des voix des écrivains autochtones GLBTQ2 d'aujourd'hui, mais également la beauté, la force et la résilience des personnes autochtones GLBTQ2 au XXIe siècle. Contributeurs : Indira Allegra, Louise Esme Cruz, Paula Gunn Allen, Qwo-Li Driskill, Laura Furlan, Janice Gould, Carrie House, Daniel Heath Justice, Maurice Kenny, Michael Koby, M. Carmen Lane, Jaynie Lara, Chip Livingston, Luna Maia , Janet McAdams, Deborah Miranda, Daniel David Moses, DM O'Brien, Malea Powell, Cheryl Savageau, Kim Shuck, Sarah Tsigeyu Sharp, James Thomas Stevens, Dan Taulapapa McMullin, William Raymond Taylor, Joel Waters et Craig Womack
Keywords: amérique du nord; amériques; approches et analyses; arts; discipline; discours dominant; féminisme autochtone; identités LGBTQIA2+; outils; ouvrages de références; queer; racisme; régions géographiques; système colonial; systèmes d'oppressions; études littéraires